A one-step conversion from gastric banding to laparoscopic Roux-en-Y gastric bypass is as safe as a two-step conversion: A comparative analysis of 885 patients. Issue 5 (2nd September 2016) - Debergh, Isabelle; Defoort, Barbara; De Visschere, Marieke; Flahou, Silke; Van Cauwenberge, Sebastiaan; Mulier, Jan P.; Dillemans, Bruno
Abstract: Aims: To achieve additional weight loss or to resolve band-related problems, a laparoscopic adjustable gastric banding (LAGB) can be converted to a laparoscopic Roux-en-Y gastric bypass (RYGB). There is limited data on the feasibility and safety of routinely performing a single-step conversion. We assessed the efficacy of this revisional approach in a large cohort of patients operated in a high-volume bariatric institution. Methods: Between October 2004 and December 2015, a total of 885 patients who underwent LAGB removal with RYGB were identified from a prospectively collected database. In all cases, a single-stage conversion procedure was planned. The feasibility of this approach and peri-operative outcomes of these patients were evaluated and analyzed. Results: A single-step approach was successfully achieved in 738 (83.4%) of the 885 patients. During the study period, there was a significant increase in performing the conversion from LAGB to RYGB single-staged. No mortality or anastomotic leakage was observed in both groups. Only 45 patients (5.1%) had a 30-d complication: most commonly hemorrhage ( N = 20/45), with no significant difference between the groups. Conclusion: Converting a LAGB to RYGB can be performed with a very low morbidity and zero-mortality in a high-volume revisional bariatric center. With increasing experience and full standardization of the conversion, the vast majority of operations can be performed as a single-stage procedure. Only a migrated band remains a formal contraindication for a one-step approach.